Analysis of the Implementation of TQM (Total Quality Management) in the Sayang Warga Program’s Innovation (Case Study at the Kendangsari Subdistrict Office, Surabaya) - Hariyoko, Yusuf; Ria, Catur Ajeng Kartika; Nugraha, Fransiskus Ari; Bella, Vivtania Salsa (Universitas Muhammadiyah Sidoarjo, 2024)
Sayang Warga is a population service program provided by the Population and Civil Registry Service of the City of Surabaya. This program emphasizes coordination and collaboration between parties from sub-districts and RWs. The aim of this research is to analyze the implementation of the Sayang Warga Program’s using TQM analysis. This research uses a descriptive qualitative approach. The results show that Kendangsari Subdistrict, in implementing community care services, has implemented good leadership. Kendangsari Subdistrict carries out routine coordination and direction. The standard operating procedures (SOP) and output issued in the service are in line with expectations. Apart from that, the community's enthusiasm for serving citizens is also very large. What needs to be considered in this service are facilities and leadership whose achievements can be measured.